DIGITAL SIMULATIONS IN ARCHITECTURAL DESIGN: CALCULATING LIGHT, ACOUSTICS, AND ENERGY EFFICIENCY - A. R. Abobakirov (Modern American Journals, 2025)
In recent decades, the field of architecture has undergone a profound transformation through the integration of digital simulation technologies, which have provided architects, engineers, and designers with unprecedented capabilities to predict, analyze, and optimize building performance in terms of light distribution, acoustic quality, and energy efficiency. This study explores the role of digital simulations in architectural design, focusing on three primary domains: daylight and artificial lighting simulations, acoustic modeling, and energy performance analysis. By reviewing the historical development of digital tools, outlining methodological approaches, and analyzing case studies from both global and Uzbek architectural practice, the research demonstrates how simulation technologies contribute to sustainable design, improve user comfort, and support compliance with environmental standards. Light simulations, performed using tools such as Radiance, DIALux, and Autodesk Revit’s daylight analysis module, have enabled architects to create spaces with optimal natural illumination, reducing reliance on artificial lighting and enhancing visual comfort. Acoustic simulations, employing programs such as ODEON, CATT-Acoustic, and EASE, have allowed precise predictions of reverberation, sound distribution, and clarity in spaces such as concert halls, mosques, and auditoriums, ensuring functional and spiritual resonance. Energy simulations, using software such as EnergyPlus, DesignBuilder, and IESVE, have facilitated the evaluation of heating, cooling, ventilation, and energy loads, enabling architects to design buildings that minimize energy consumption while maintaining comfort. The findings indicate that digital simulations not only improve the technical performance of buildings but also enable architects to preserve cultural identity, integrate heritage values, and address the unique environmental challenges of Central Asia. The discussion emphasizes that while simulation technologies offer precision and predictive capacity, their effectiveness depends on accurate input data, interdisciplinary collaboration, and contextual adaptation. The conclusion underscores that digital simulations represent a cornerstone of contemporary architectural practice, aligning with global trends in sustainable development and offering Uzbekistan a pathway to integrate advanced technologies with its rich architectural heritage.
Keywords: Digital Simulation; Architecture; Daylight Analysis; Acoustic Modeling; Energy Efficiency; Sustainable Design; Uzbekistan